Prognostic Factors at Diagnosis Associated With Damage Accrual in Childhood-Onset Systemic Lupus Erythematosus Patients - Rodríguez-Lozano, Ana Luisa; Rivas-Larrauri, Francisco Eduardo; García-de la Puente, Silvestre; Alcivar-Arteaga, Daniel Alfredo; González-Garay, Alejandro Gabriel (Frontiers in Pediatrics, 2022)
Objectives: To associate prognostic factors present at diagnosis with damage accrual in childhood-onset systemic lupus erythematosus (cSLE) patients. Methods: We designed a cohort study where children aged 16 or below and fulfilled the 1997 American College of Rheumatology (ACR) classification criteria for SLE were eligible; we excluded those with previous treatment with steroids or immunosuppressants. The diagnosis date was cohort entry. We followed up on all subjects prospectively for at least two years. Two experts assessed the disease activity with the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and Mexican-SLEDAI (MEX-SLEDAI) every 3 to 6 months. Damage was measured annually, applying Pediatric Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI) to their last visit. We analyzed prognostic factors by relative risks (RR) and used logistic regression to construct the clinimetric table. Results: Ninety patients with a median age of 11.8 years at diagnosis had a SLEDAI score of 15.5 (2 to 40) and a MEX-SLEDAI score of 12 (2 to 29); of them, forty-eight children (53%) had SDI ≥ 2. The associated variables to damage (SDI ≥ 2) are as follows: neurologic disease RR 9.55 [95% CI 1.411 to 64.621]; vasculitis RR 2.81 [95% CI 0.991 to 7.973], and hemolytic anemia RR 2.09 [95% CI 1.280 to 3.415]. When these three features are present at diagnosis, the probability of damage ascends to 98.97%. Conclusion: At diagnosis, we identified neurologic disease, vasculitis, and hemolytic anemia as prognostic factors related to the development of damage in cSLE. Their presence should lead to a closer follow-up to reduce the likelihood of damage development.